Association of plasma uric acid levels with cognitive function among non-hyperuricemia adults: A prospective study. Issue 3 (March 2022) - Huang, Yuhui; Zhang, Shen; Shen, Jiadong; Yang, Jiaxi; Chen, Xiao; Li, Wanlu; Wang, Jiawen; Xu, Xiaolin; Xu, Xin; Liu, Zuyun; Li, Xue; Ma, Yanan; et al.
Summary: Background & aims: The neuroprotective roles of uric acid are still controversial. One possible explanation is that previous studies included participants with hyperuricemia, which might interfere with clarifying the association. Therefore, this study aimed to investigate the prospective association between plasma uric acid levels and cognitive function among non-hyperuricemia adults. Methods: A total of 7828 participants from the China Health and Retirement Longitudinal Study (CHARLS) who were free from hyperuricemia, brain damage, mental retardation, or memory-related diseases at baseline were included. According to the baseline plasma uric acid levels, participants were classified into low (<3.5 mg/dL for men and <2.5 mg/dL for women), low-normal (3.5–4.9 mg/dL for men and 2.5–3.9 mg/dL for women), and high-normal groups (4.9–7.0 mg/dL for men and 3.9–6.0 mg/dL for women). Cognitive function tests covered the domains of executive function (time orientation, numerical ability, and drawing) and episodic memory (immediate and delayed word recall). We used generalized estimating equation models to evaluate the average difference in cognitive function within 4-years' follow-up across different uric acid groups. Results: Compared with the high-normal group, participants with lower uric acid levels were associated with poorer cognitive performance during 4-years' follow-up. The corresponding level of difference was −0.24 (95% CI: −0.47, −0.01) for low group, and −0.13 (95% CI: −0.26, −0.01) for low-normal group. The associations were significant and similar for the specific domain of executive function ( P < 0.001). In addition, a stronger association was observed among participants with baseline age ≥60 years ( P < 0.05 for interaction). Conclusions: Our study supports a potential detrimental role of low levels of plasma uric acid on cognitive function among Chinese adults without hyperuricemia. More research is warranted to confirm this finding and identify the optimal plasma uric acid level for cognitive benefits.